Composite body and float
A composite molded body with a polylactic acid resin foam covered by a durable skin material addresses the durability issues of polylactic acid floats, providing a lightweight and environmentally friendly solution.
Patent Information
- Application Number
- JP2024003615U
- Authority / Receiving Office
- JP · JP
- Patent Type
- Utility models
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2034-10-31
AI Technical Summary
Existing floats made of polylactic acid resin are lightweight but lack durability, posing challenges in environmental and durability demands.
A composite molded body comprising a synthetic resin foam covered with a skin material made of a thermoplastic resin blow molded product, where the skin material contains polylactic acid resin modified with a chain extender, having specific melt tension and thickness, and optionally mixed with other thermoplastic resins, ensuring excellent durability and buoyancy.
The composite molded product is lightweight and durable, suitable for use as a float with improved impact resistance and environmental friendliness.
Smart Images

Figure 0003249658000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite molded article that can be used as a float and that includes a synthetic resin foam and a skin material that is made of a blow molded article that covers the synthetic resin foam. [Background technology]
[0002] A float, also called a floater, is a tool used to make things float underwater or on the water surface. In the past, floats were made from cork, wood, bamboo, or glass, but most floats today are made from synthetic resin. Furthermore, foam floats made from foamed resin are light in weight for their size and have high buoyancy, so they are widely used in fishery-related fields such as aquaculture ponds.
[0003] On the other hand, due to the recent increase in environmental awareness, there is a demand for floats made of environmentally friendly materials. For example, in the FY2022 Fisheries-related Marine Plastic Waste Reduction Project, an attempt was made to create floats using polylactic acid, a plant-derived plastic, as an alternative material to polyethylene. However, this float had issues with its light weight and durability. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2006-27541 A Summary of the Invention [Problem to be solved by the invention]
[0005] In view of the above circumstances, the present invention aims to provide a lightweight and durable composite molded body using a polylactic acid-based resin as a material for the skin, the composite molded body comprising a skin made of a thermoplastic resin blow molded body and a synthetic resin foam covered with the skin, and a float made of the composite molded body. [Means for solving the problem]
[0006] According to the present invention, there is provided a float as follows. [1] A composite molded product comprising a synthetic resin foam and a skin material formed of a thermoplastic resin blow molded product covering the synthetic resin foam, The resin constituting the skin material contains a polylactic acid-based resin as a base resin, the polylactic acid resin is modified with a chain extender, and the melt tension of the skin material at 190°C is 50 mN or more and 450 mN or less; The average thickness of the skin material is 1 mm or more and 5 mm or less. [2] The composite molding according to [1] above, wherein the resin constituting the skin material is a mixed resin of a polylactic acid resin and a thermoplastic resin (A) having a flexural modulus of 500 MPa or less. [3] The composite molding according to [1] or [2], wherein the resin constituting the skin material is a mixed resin of the polylactic acid resin and polybutylene succinate and / or polybutylene adipate terephthalate. [4] The composite molded product according to any one of the above [1] to [3], wherein the synthetic resin foam is a polylactic acid resin foamed bead molded product. [5] The composite molded body according to any one of the above [1] to [4], wherein the chain extender is a compound having a plurality of functional groups selected from an epoxy group, a carbodiimide group, an oxazoline group, and an isocyanate group. [6] The composite molded product according to any one of the above [1] to [5], wherein the chain extender is an acrylic polymer containing a plurality of epoxy groups. [7] The density of the composite compact is 15 kg / m 3 More than 250kg / m 3 The composite molding according to any one of the above [1] to [6], which is as follows: [8] The total volume of the composite compact is 0.05 m 3 More than 0.5m3 The composite molding according to any one of the above [1] to [7], which is as follows: [9] A float comprising the composite molded article according to any one of the above [1] to [8]. Effect of the Invention
[0007] The composite molded product of the present invention is lightweight and has excellent durability, as it is constructed by covering a synthetic resin foam with a thin blow molded body using a specific resin with a polylactic acid-based resin as the base resin. These characteristics make the composite molded product of the present invention suitable for use as a float. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a partially cutaway perspective view showing an example of a composite molded body according to the present invention. [Diagram 2] FIG. 2 is a diagram showing an example of a float made of a composite molded body according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The composite molding of the present invention will be described in detail below. The composite molded article of the present invention is a composite molded article having a skin material and a synthetic resin foam, and the skin material covers the synthetic resin foam. An example of the composite molded body is shown in Figure 1. In Figure 1, 1 indicates the composite molded body, 2 indicates the skin material, and 3 indicates the synthetic resin foam.
[0010] In the present invention, the skin material is formed of a thermoplastic resin blow molded body (hereinafter, sometimes simply referred to as a blow molded body). The skin material is formed of a blow molded body, and the composite molded body has excellent durability. Specifically, a hollow blow molded body, a sheet blow molded body, etc. can be mentioned, and a hollow blow molded body is preferable. In hollow blow molding, for example, a cylindrical parison made of a molten polylactic acid-based resin is hung between split dies, the parison is sandwiched using a pinch or the like to close the lower part, air is blown into the parison, the split dies are closed, and the parison is deformed so as to fit the molding surfaces of a pair of split dies, thereby forming a blow molded body.
[0011] In the present invention, the thermoplastic resin constituting the skin material contains a polylactic acid resin as a base resin. The polylactic acid is a polymer of monomer units derived from L-lactic acid and / or D-lactic acid. However, the polylactic acid resin may be copolymerized with monomer components other than lactic acid as long as the properties of polylactic acid are not impaired. The content of components derived from lactic acid monomers in the polylactic acid resin is preferably 50% by mass or more, more preferably 75% by mass or more, and even more preferably 96% by mass or more. The molecular weight of the polylactic acid resin is preferably 50,000 to 500,000 in terms of weight average molecular weight, from the viewpoint of a good balance between mechanical properties and moldability.
[0012] In this invention, use as a base resin means that it is composed of the main component of the thermoplastic resin that constitutes the skin material, and preferably, 50% or more of the resin that constitutes the skin material is polylactic acid, and more preferably, 70% or more of the resin that constitutes the skin material is a polylactic acid-based resin.
[0013] The skin material made of the polylactic acid resin must have a melt tension at 190° C. of 50 mN or more and 450 mN or less. If the melt tension is within this range, it is possible to form a composite molded article covered with a synthetic resin foam by using a skin material formed from a blow molded article.
[0014] If the melt tension is too low, when forming the skin material, the parison may sag or be partially stretched and broken, making it difficult to form the blow molded body. From this viewpoint, the lower limit of the melt tension is preferably 50 mN, more preferably 70 mN, and even more preferably 90 mN. On the other hand, the upper limit of the melt tension is preferably 450 mN, more preferably 350 mN, and even more preferably 300 mN. In addition, in the present invention, the melt viscosity at 190°C of the skin material made of the polylactic acid resin is preferably 1000 Pa·s or more and 5000 Pa·s or less, more preferably 1200 Pa·s or more and 4000 Pa·s or less, and even more preferably 1500 Pa·s or more and 3000 Pa·s or less, because the blow moldability is excellent. In addition, the ratio of the melt viscosity to the melt tension is preferably 5 to 50, and more preferably 8 to 30.
[0015] In this specification, melt tension is measured as follows. It can be measured by a measurement method using an accelerated winding method using a Capillograph 1D manufactured by Toyo Seiki Seisakusho Co., Ltd. Specifically, a cylinder with a cylinder diameter of 9.55 mm and a length of 350 mm and a nozzle diameter of 2.095 mm and a length of 8 mm are used, the set temperature of the cylinder and the orifice is set to 190°C, and a required amount of a measurement sample that has been thoroughly dried at 70°C is placed in the cylinder, and after leaving it for 4 minutes, the molten resin is extruded in a string shape at a piston speed of 10 mm / min, and this string-like material is hung on a tension detection pulley with a diameter of 45 mm, and the string-like material is taken up by a take-up roller while increasing the take-up speed at a constant rate so that the take-up speed reaches 200 m / min from 0 m / min in 10 minutes, and the maximum value detected by the device when the string-like material breaks is taken as the melt tension. Note that if the string-like material does not break at a take-up speed of 200 m / min, the value detected by the device at a take-up speed of 200 m / min is adopted as the melt tension. The above procedure is carried out ten times using different samples, and the three largest maximum values and the three smallest maximum values obtained from the ten times are removed. The arithmetic mean of the remaining four intermediate maximum values is defined as the melt tension (mN) in this invention. The measurement sample is a cut-out sample of the obtained skin material.
[0016] In this specification, the melt viscosity is based on JIS K7199:1999 at a temperature of 190°C and a shear rate of 100 sec -1 The melt viscosity is a value measured under the following conditions: A specific method for measuring the melt viscosity will be described in the Examples.
[0017] In the present invention, since the skin covering the synthetic resin foam is a blow molded product, it is easy to form a state in which at least 80% of the surface area of the synthetic resin foam is covered with the skin. By covering the synthetic resin foam with a blow molded product, durability is improved, and when used as a float, cracking or chipping of the synthetic resin foam is prevented, and the foam particles can be effectively prevented from leaking out. The coverage ratio is preferably 90% or more, and more preferably 95% or more.
[0018] Various additives can be added to the resin constituting the skin material. Examples of the additives include colorants, flame retardants, lubricants, antioxidants, weathering agents, plasticizers, etc. The amount of these various additives added varies depending on the purpose and use, but is preferably 10 parts by mass or less per 100 parts by mass of the resin constituting the skin material. More preferably, it is 5 parts by mass or less, and even more preferably, it is 3 parts by mass or less. In addition, examples of the plasticizer include ester-based plasticizers such as phthalate ester-based plasticizers, adipate ester-based plasticizers, and phosphate ester-based plasticizers, and acrylic plasticizers, and the impact resistance of the resin constituting the skin material can be improved by adding these.
[0019] In the present invention, the polylactic acid resin is a resin modified with a chain extender. Specifically, by using a resin modified with a chain extender, it is possible to set the skin thickness of the blow molded article constituting the skin material within the range specified in the present invention. If the polylactic acid-based resin is not modified, the melt tension (hereinafter also referred to as MT) of the resin constituting the skin material is low, which may make it difficult to form a blow molded body with the skin thickness specified in this invention.
[0020] The chain extender may be a compound having reactivity with polylactic acid resins that involves chain extension, such as a compound having a plurality of functional groups selected from epoxy groups, carbodiimide groups, oxazoline groups, and isocyanate groups. For example, by using these chain extenders to heat-treat a polylactic acid resin, polylactic acid reacts and bonds with a plurality of functional groups, thereby increasing the melt tension (MT). As a result, drawdown of the parison during blow molding is prevented, and even if there is a portion of the mold shape that is highly retracted, the parison is prevented from being partially stretched or broken, and the blow molded body can be used as a skin material for a composite molded body. The modification treatment may be performed during heating during blow molding, or a polylactic acid resin that has been modified in advance may be used.
[0021] Polylactic acid is a polymer in which lactic acid is polymerized through ester bonds to form long chains. Since it has carboxyl groups (COOH), it can be modified to form even longer polymers by using reactive groups that undergo esterification (R-COO-R'), such as epoxy groups, carbodiimide groups, oxazoline groups, and isocyanate groups. In addition, since polylactic acid also has hydroxyl groups (OH), it can be modified by using isocyanate groups or carbodiimide groups that react with the hydroxyl groups, and the above-mentioned effects can be obtained.
[0022] The chain extender is preferably an acrylic polymer containing multiple epoxy groups. The epoxy group reacts with the carboxyl group (COOH) of polylactic acid to link the polylactic acid with the acrylic polymer, and can elongate the polylactic acid. When the chain extender is an acrylic polymer containing multiple epoxy groups, the epoxy value of the chain extender is preferably 1 to 10 meq / g, more preferably 1.5 to 7 meq / g. The epoxy equivalent of the chain extender is preferably 100 to 1000 g / eq., more preferably 150 to 800 g / eq. The chain extender is preferably blended in an amount of 0.1 to 10 parts by mass, more preferably 0.3 to 5 parts by mass, and even more preferably 0.5 to 3 parts by mass, relative to 100 parts by mass of the thermoplastic resin constituting the skin material. Specific examples of available acrylic polymers include "ARUFON UG-4035" manufactured by Toagosei Co., Ltd. and "Marproof G01100" manufactured by NOF Corporation.
[0023] In the present invention, the resin constituting the skin material is preferably a mixed resin of a polylactic acid-based resin and a thermoplastic resin (A) having a flexural modulus of 500 MPa or less (hereinafter, sometimes simply referred to as resin (A) and excluding the polylactic acid-based resin). The use of the above-mentioned mixed resin can further improve the impact resistance. When resin (A) is used, it is sufficient that at least the polylactic acid resin constituting the base resin has been modified, and that the skin material has a melt tension within the above-mentioned specific range.
[0024] The blending ratio of the polylactic acid resin and resin (A) in the mixed resin is preferably 50 to 90 mass% of the polylactic acid resin and 10 to 50 mass% of resin (A) (wherein the sum of the polylactic acid resin and resin (A) is 100 mass%), and more preferably 60 to 80 mass% of the polylactic acid resin and 20 to 40 mass% of resin (A).
[0025] One method for improving the impact resistance of the composite molding is to increase the thickness of the skin material, but this increases the mass and reduces the buoyancy when used as a float. By using a mixed resin containing the resin (A) in addition to the polylactic acid resin, the impact resistance of the skin material can be improved. From the viewpoint of improving impact resistance, the flexural modulus of the resin (A) constituting the mixed resin is preferably 10 MPa or more and 400 MPa or less, and more preferably 30 MPa or more and 300 MPa or less.
[0026] Examples of the resin (A) include polyethylene resins, polyester resins, thermoplastic elastomers, etc. Among these, the resin (A) is preferably polybutylene adipate terephthalate and / or polybutylene succinate.
[0027] Polybutylene adipate terephthalate is a petroleum-derived biodegradable resin, a type of polyester made from terephthalic acid and 1,4-butanediol. Commercially available products include BASF's Ecoflex (flexural modulus 60 MPa).
[0028] Polybutylene succinate is mainly produced from petroleum, but can also be synthesized from plants. It is obtained by synthesizing succinic acid and 1,4-butanediol to produce PBS oligomers, and then transesterifying these oligomers under vacuum to produce high molecular weight polymers. Commercially available products include Mitsubishi Chemical's BioPBS FZ91PB (flexural modulus 375 MPa). These resins can improve the impact resistance, and when a plant-derived resin or a biodegradable resin is used, a composite molding can be made that is more environmentally friendly.
[0029] In the composite molded product of the present invention, the average thickness of the skin material is 1 mm or more and 5 mm or less. If the average thickness is within this range, a composite molded product having an excellent balance between durability and light weight can be obtained. In particular, it is preferable that the blow molded product as the skin material constituting the composite molded product of the present invention is non-foamed and thin-walled. The fact that the blow molded product is thin-walled can greatly contribute to the light weight of the composite molded product, and the fact that it is non-foamed can prevent a decrease in strength. If the average thickness is too small, the strength may decrease, resulting in a composite molding that is easily damaged. On the other hand, if the average thickness is too large, when the composite molding is used as a float, the lightness may be impaired. From this viewpoint, the lower limit of the average thickness is preferably 1.2 mm, more preferably 1.5 mm. On the other hand, the upper limit of the average thickness is preferably 4 mm, more preferably 3 mm.
[0030] In the present invention, the resin constituting the synthetic resin foam can be any resin that can be molded into a synthetic resin foam. For example, polystyrene-based resins such as polystyrene and high-impact polystyrene, polypropylene-based resins such as homopolypropylene, random polypropylene, and block polypropylene, polyethylene-based resins such as low-density polyethylene and linear low-density polyethylene, polyester-based resins such as polylactic acid-based resins, polyurethane-based resins, etc. are included. Among these, thermoplastic resins are preferred, and polystyrene-based resins, polypropylene-based resins, and polylactic acid-based resins are more preferred.
[0031] The synthetic resin foam is preferably a foamed bead molding obtained by molding foamed beads in a mold. Examples of the foamed beads constituting the foamed bead molding include commercially available polylactic acid resin foamed beads (LACTIF (registered trademark)), polystyrene resin foamed beads (STYRODIA (registered trademark)), and polypropylene resin foamed beads (ARPRO (registered trademark)) manufactured by JSP.
[0032] In the present invention, the synthetic resin foam is preferably a polylactic acid resin foamed bead molding. In this case, the higher the content of polylactic acid resin foamed beads in the foamed bead molding, the more environmentally friendly the product can be, so the content is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, 80% by mass or more, 90% by mass or more, and particularly preferably 96% by mass or more.
[0033] The polylactic acid resin constituting the expanded polylactic acid resin particles constituting the expanded particle molding can be the same as the polylactic acid resin used as the skin material.
[0034] The density of the composite molding of this invention is 15kg / m 3 More than 250kg / m 3 It is preferable that: If the green compact density is within the above range, for example, the balance between buoyancy when used as a float and strength such as resistance to deformation is excellent. If the green compact density is too low, the strength of the composite green compact may be too low. On the other hand, if the green compact density is too high, the buoyancy when used as a float may be too low. From this viewpoint, the lower limit of the green compact density is 20 kg / m 3 is preferable, and more preferably 30 kg / m 3 , more preferably 40 kg / m 3 On the other hand, the upper limit of the density of the compact is 200 kg / m 3 is preferable, and more preferably 180 kg / m 3 , more preferably 140 kg / m 3 , particularly preferably 100 kg / m 3 It is.
[0035] The total volume of the composite molding of this invention is 0.05m 3 More than 0.5m 3It is preferable that the total volume is not more than 0.1 m. If the total volume is within the above range, the composite molding will have excellent handleability and workability. If the total volume is too small, for example when used as a float, the number of floats will be too large, making the work complicated and reducing the workability. On the other hand, if the total volume is too large, for example when used as a float, the floats will be too large and difficult to handle, reducing the workability. From this viewpoint, the lower limit of the total volume is 0.1 m. 3 On the other hand, the upper limit of the total volume is 0.4 m 3 is preferable, and 0.3 m is more preferable. 3 It is.
[0036] The total volume of the composite molding can be determined by three-dimensional measurement.
[0037] The composite molded article of the present invention has a large buoyancy and is therefore ideal for use as a float. The float is environmentally friendly and has excellent durability. EXAMPLES
[0038] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, the following raw materials were used.
[0039] (Polylactic acid resin) Abbreviation "2003D": Polylactic acid resin; NatureWorks "IngeoBioPolymer2003D" (density 1240 kg / m 3 , melting point = 150 °C Tg = 60 °C)
[0040] (Polymer with flexural modulus of 500 MPa or less) (1) Abbreviation "C1200": Polybutylene adipate terephthalate; BASF "Ecoflex C1200" (melting point 115°C, Tg = -28°C). Detailed physical properties are shown in Table 1. (2) Abbreviation "FZ91PB": polybutylene succinate; "BioPBS FZ91PB" manufactured by Mitsubishi Chemical (melting point 113°C). Detailed physical properties are shown in Table 1.
[0041] [Table 1]
[0042] (Chain extender) (1) Abbreviation "ARUFON": Epoxy group-containing acrylic polymer; "ARUFON UG-4035" (density 1140 kg / m) manufactured by Toa Gosei Co., Ltd. 3 , epoxy value 1.8 meq / g, epoxy amount per 1 mol 19.8 eq / mol, glass transition temperature 52°C, weight average molecular weight 11000) (2) Abbreviation "Marproof": Epoxy group-containing acrylic polymer; NOF Corporation "Marproof G01100" (epoxy equivalent 170g / eq, epoxy amount per 1mol 58.8eq / mol, glass transition temperature 47°C, weight average molecular weight 10000) Detailed properties of various chain extenders are shown in Table 2.
[0043] [Table 2]
[0044] (Foamed bead molding) The expanded beads used to form the expanded bead molding were as follows: (1) Abbreviation: "EPLA"; polylactic acid resin expanded particles; LACTIF (registered trademark) 20 times expanded product (2) Abbreviation "EPS": polystyrene resin expanded particles; Styrodia (registered trademark) 50 times expanded product (3) Abbreviation "EPP": Polypropylene resin expanded particles; ARPRO (registered trademark) 30 times expanded product
[0045] (Weatherproofing agent) A 3% masterbatch of a mixture of a commercially available UV absorber and a hindered amine-based light absorber was used.
[0046] (Device) An accumulator was installed at the outlet of an extruder with an inner diameter of 65 mm, and an extrusion device was used in which a die capable of extruding a cylindrical parison was attached downstream of the accumulator, and a blow molding device was used that could blow mold the extruded softened parison and mold a foamed bead molding inside the hollow body.
[0047] Examples 1 to 18, Comparative Examples 1 to 11 [Blow molding process] The polylactic acid resin, resin (A), chain extender, and weather resistance agent shown in Table 3 (Examples), Table 4 (Examples), Table 5 (Comparative Examples), and Table 6 (Comparative Examples) were supplied to an extruder having an inner diameter of 65 mm, and the resin was heated and melted in the extruder set at 200°C, thereby modifying the polylactic acid resin and producing a resin molten mixture. When preparing a mixed resin with resin (A), resin (A) was added together with the polylactic acid resin and the same treatment was carried out.
[0048] The resin melt-kneaded material was filled into an accumulator set at (200)°C, and then extruded as a cylindrical parison from a die attached downstream of the accumulator. The clearance of the die lip was 4 mm, and the die temperature was set at 200°C.
[0049] The softened parison was placed in an open cylindrical mold (dimensions of the molding space inside the mold: diameter 600 mm x height 1060 mm, total volume 0.27 m) with a float shape capable of molding the float shown in Figure 2, which was placed directly under the die. 3 ) was placed between them. The temperature of the mold was set to 50°C. After the mold was closed to sandwich the parison between the molds, a blow molding pin (blow pin) was driven into the parison and air pressurized to 0.50 MPa (G) ((G) indicates gauge pressure) was blown into the parison from the blow pin, while at the same time reducing the pressure between the outer surface of the parison and the inner surface of the mold, to form a skin material (hollow molded body).
[0050] [Foam particle filling process] After the mold was clamped, a steam pin having a slit-shaped steam supply port was driven into the hollow molded body from one side of the mold toward the thickness direction of the molding space, and a feeder for filling foamed particles was driven into the hollow molded body. After completion of the driving, the steam pin was vented while the internal pressure of the hollow molding was released, and the hollow portion of the hollow molding was filled with foamed beads capable of forming the foamed bead moldings shown in Tables 3, 4, 5, and 6 from the foamed bead filling feeder.
[0051] [Fusing process] After the pre-expanded particle filling step was completed, steam was supplied from one steam pin inserted between the filled pre-expanded particles while exhausting from the other steam pin. Next, the steam pin that had been supplying steam was exhausted, and steam was supplied from the other steam pin that had been exhausted, and alternating heating was performed twice. This caused the foamed particles to fuse together in the hollow molded body. In Examples 6, 10, and 15, after alternating heating was performed once, steam was supplied from all steam pins to fuse the foamed particles.
[0052] The foamed bead molding was cooled while exhausting the steam by a steam pin inserted in the foamed bead molding. After that, the mold was opened to take out the foamed bead molding with skin (composite molding). The burrs of the composite molding were appropriately removed. The average thickness of the skin material of the obtained composite molding, the density of the composite molding, the average thickness of the skin material, the melt tension of the skin material, the melt viscosity of the skin material, the drop test result of the skin material, and the 23°C Charpy impact value of the skin material are shown in Tables 3, 4, 5, and 6. In the composite molding obtained by the method of the embodiment, the foamed bead molding has a structure in which the foamed bead molding is covered with the blow molding, and the coverage is 90% or more. In addition, when the foamed bead molding and the blow molding are formed from the same type of resin, the skin material and the foamed bead molding can be fused and integrated at the same time in the fusion process of the foamed bead molding, resulting in a more excellent durability.
[0053] [Table 3]
[0054] [Table 4]
[0055] [Table 5]
[0056] [Table 6]
[0057] The various physical properties in the table were measured as follows. (Composite compact density) The density of the composite compact was determined by first measuring the total volume of the composite compact by three-dimensional measurement, then measuring the mass of the composite compact, and dividing the mass of the compact by the volume of the composite compact determined by the three-dimensional measurement.
[0058] (average thickness of skin material) The average thickness of the skin material in the composite molded body was measured at three vertical cross sections in the longitudinal direction of the composite molded body, one near the longitudinal center and one near both longitudinal ends. The thickness of the skin material in the thickness direction of six vertical cross sections was measured at equal intervals along the circumferential direction of the skin of each vertical cross section, and the arithmetic mean value of the thicknesses obtained at 18 points (average thickness of the skin material) was taken as the average thickness of the skin material.
[0059] (melt tension of skin material) The measurement was performed by the above-mentioned method.
[0060] (Melt viscosity of skin material) The melt viscosity of the skin material was measured using a measuring device such as Capillograph 1D manufactured by Toyo Seiki Seisakusho Co., Ltd. Specifically, a cylinder with a cylinder diameter of 9.55 mm and a length of 350 mm and an orifice with a nozzle diameter of 1.0 mm and a length of 10 mm were used, the set temperatures of the cylinder and orifice were set to 190°C, and a required amount of the measurement sample that had been sufficiently dried at 70°C was placed in the cylinder and left for 4 minutes, and then heated at a shear rate of 100 sec. -1 The molten resin was extruded in a string shape from the orifice, and the melt viscosity at that time was measured.
[0061] (Drop test) The composite molding was dropped from a height of 1.4 m in an atmosphere of 23° C., and the condition of the skin material was observed and evaluated according to the following criteria. ⊚: No cracks or fissures were observed in the skin material. ◯: Cracks were generated in some parts of the skin material, but exposure of the foamed bead molding was prevented. ×: Cracks occurred in the skin material.
[0062] (Charpy impact value of skin material at 23℃) The Charpy impact value was measured based on JIS K7111-1:2012.
[0063] In Examples 1 to 18, when the configuration of the present invention is satisfied, the composite molded body is a lightweight and durable composite molded body, since it is a composite molded body having a skin material formed from a blow molded body of a specific thickness using polylactic acid as a base resin. Therefore, the obtained composite molded body can be used as a float. On the other hand, in Comparative Examples 1 to 11, when the configuration of the present invention is not satisfied, when polylactic acid is used as a base resin, it is not possible to obtain a composite molded body having a skin material formed from a blow molded body of a specific thickness, and it is further not possible to obtain a lightweight and durable composite molded body.
Claims
1. A composite molded product comprising a synthetic resin foam and a skin material made of a thermoplastic resin blow molded product covering the synthetic resin foam, The thermoplastic resin constituting the skin material contains a polylactic acid-based resin as a base resin, The polylactic acid resin is modified with a chain extender, The skin material has a melt tension of 50 mN or more and 450 mN or less at 190°C, The average thickness of the skin material is 1 mm or more and 5 mm or less.
2. 2. The composite molding according to claim 1, wherein the thermoplastic resin constituting the skin material is a mixed resin of the polylactic acid resin and a thermoplastic resin (A) having a flexural modulus of 500 MPa or less.
3. 3. The composite molding according to claim 1, wherein the thermoplastic resin constituting the skin material is a mixed resin of the polylactic acid resin and polybutylene succinate and / or polybutylene adipate terephthalate.
4. 3. The composite molded article according to claim 1, wherein the synthetic resin foam is a polylactic acid resin foamed bead molded article.
5. 3. The composite molded article according to claim 1, wherein the chain extender is a compound having a plurality of functional groups selected from the group consisting of epoxy groups, carbodiimide groups, oxazoline groups and isocyanate groups.
6. 3. The composite molding according to claim 1, wherein the chain extender is an acrylic polymer containing a plurality of epoxy groups.
7. The density of the composite compact is 15 kg / m 3 More than 250kg / m 3 3. The composite molding according to claim 1 or 2, wherein:
8. The total volume of the composite molding is 0.05 m 3 0.5m or more 3 3. The composite molding according to claim 1 or 2, wherein:
9. A float comprising the composite molding according to claim 1 or 2.
Citation Information
Patent Citations
Float
JP2006027541A